(untitled) (Prilozi za orijentalnu filologiju, 2017)
In the book Uspomene iz Hrvatske [Memoirs from Croatia] by the Croatian writer Imbro Tkalac (1824-1912) who was born and raised in Karlovac, there is an account of the author’s visit to the Bosnian town of Bihać. In about 1841 he spent several days there as a guest of Mehmed Bey and established friendly relationship with his son. In this paper, Tkalac’s narrative is approached as a testimony to an unofficial, personal encounter of the inhabitants from different sides of the Habsburg- Ottoman border. By its relatively calm rhetorics and balanced judgements it stands in contrast with the well-known Croatian travelogue Pogled u Bosnu [A Look at Bosnia] written by Matija Mažuranić who travelled to Bosnia in the same period. The comparison of the two texts shows the impact of ideological and educational background, as well as the intellectual openness of the observer, on the formation of his views on a different culture.